MODERN UNDERSTANDING OF REGULATORY IMPACT ASSESSMENT AS A MEANS OF IMPROVING LEGISLATION - Bobur Mukumov (Modern American Journals, 2026)
The article analyzes the assessment of regulatory impact as a tool for improving the quality and effectiveness of legislative regulation. The main approaches to understanding the assessment of legislation in foreign legal doctrine and practice, as well as institutional and procedural forms of its application, are considered. Special attention is paid to the experience of European states and OECD member countries, as well as to the implementation of regulatory impact assessment in the Republic of Uzbekistan. The necessity of forming a national ODS model is substantiated, taking into account the peculiarities of the legal system and the priorities of law-making policy.
Keywords: assessment of regulatory impact; quality of legislation; legislative regulation; law-making activities; foreign experience; legal monitoring; institutional assessment mechanisms; socio-economic consequences